Local Government Administration And The Development Of Informal Economic Sector In Nigeria: A Study Of Yenegoa Local Government Area, Bayelsa State - Abeki, Sunny Okoro (Advances in Social Sciences Research Journal, 2020)
This study examined local gove rnment policy on informal economic activities and its development Implications. The study used descriptive survey design and also sampled two hundred respondents using purposive sampling technique. The study was guided by Three research questions and objectives in line with the statement of problem. The study extensively reviewed existing literature on the subject matter with focus on government approach towards the development of informal economic sector in Yenegoa .Problems and challenges of the sector was also look at.From the analysis the study found out that there exist no concrete local government policy on the informal economic activities in Yenegoa local government which eventually is the capital of Bayelsa.The lack of policy created poor coordination of the sector and by extension loss of developmental revenue.The lack of policy also hinder the council proper provision of micro credit facility to the sector.These problem culminated to the use of available space including the roads by retailers and road side traders to carry out trading activities.The lack of policy has made all maner of persons to collect illegal taxes from those involve in the informal economic activities.Based on these findings the study recommends among others adequate policy regulations and provision of micro credit to boost economic activities at the informal sector.